Behavioral Interventions to Attenuate Driven Overeating and Weight Regain After Bariatric Surgery - Ames, Gretchen E.; Koball, Afton M.; Clark, Matthew M. (Frontiers in Endocrinology, 2022)
Weight regain after bariatric surgery is associated with problematic eating behaviors that have either recurred after a period of improvement or are new onset behaviors. Problematic eating behaviors after bariatric surgery have been conceptualized in different ways in the literature such as having a food addiction and experiencing loss of control eating. The intersection of these constructs appears to be driven overeating defined as patients’ experience of reduced control of their eating which results in overeating behavior. The purpose of this review is to define patient experiences of driven overeating through behavioral expression of emotion-based eating, reward-based eating, and executive functioning deficits—namely impulsivity—which are associated with weight regain after having bariatric surgery. Delineating concepts in this way and determining treatment strategies, accordingly, may reduce distress related to the inevitable return of increased hunger, cravings, portion sizes, and tolerance for highly palatable foods after surgery. Along with standard behavioral weight maintenance strategies, topics including acceptance, motivation, emotion-based eating, reward-based/impulsive eating, physical activity, and self-compassion are discussed. These concepts have been adapted for patients experiencing weight regain after having bariatric surgery and may be particularly helpful in attenuating driven overeating and weight regain.